A New Policy Narrative for Pastoralism? Pastoralists as Reliability Professionals and Pastoralist Systems as Infrastructure - Roe, Emery (ESRC STEPS Centre, 2020)
This paper proposes that pastoralist systems are better treated, in aggregate, as a global critical infrastructure. The policy and management implications that follow are significant and differ importantly from current pastoralist policies and recommendations. A multi-typology framework is presented, identifying the conditions under which pastoralists can be considered real-time reliability professionals in systems with mandates preventing or otherwise avoiding key events from happening. The framework leads to a different policy-relevant counternarrative to pastoralism as understood today. Some features of the counternarrative are already known or have been researched. The paper’s aim is to provoke further work (including case research and interactions with decisionmakers) on how robust the counternarrative is as a policy narrative for recasting today’s pastoralist policy and management interventions.
Accepted: 2020-01-14T10:22:59Z

Transformative project design - Kehrer, Daniel (GIZ, 2020)
There are many definitions of the term ‘transformation’ or ‘transformational change’. The first section of the report develops a basic understanding of transformations or transitions (used synonymously) viewed from various perspectives. In this, transformations are defined as processes that use disruptive innovations to change systems into fundamentally new systems that subsequently form the new mainstream. Section two describes existing approaches to environmental and climate finance in international cooperation and discusses them in light of the proposed definition. All of the approaches have the potential to be further refined and in that process often to increase the precision of what is understood by each type of transformation. The definitions already state which criteria and indicators are referred to and how relevant they are. There is wide diversity in the type of criteria and indicators used by the various organisations, and how they are classified, but certain common features can be identified and with the aid of the literature on transformations they can be combined to form a comprehensive framework. With this in mind, the derivation of quality criteria for transformative interventions is explained in section 3.1. Transformational change at one and the same time calls for big decisions and innumerable projects in a particular field of transformation; the projects cannot be planned on the drawing board but still should be coordinated with each other. Section 3.2 offers guidance on this. Section 3.3 argues in favour of focusing more closely on the ‘process promise’ and employing a more iterative and more adaptable commissioning procedure. Finally, section 3.4 introduces two types of indicators under the various criteria: design indicators, which measure the quality of interventions that are aimed at influencing transformations (process orientation), and outcome indicators, which measure the process and/or progress of a transformation itself.

Transforming our work: Getting ready for transformational projects - Kehrer, Daniel; Flossmann-Kraus, Ursula; Ronco Alarcon, Sabrina Valeria; Albers, Vivien; Aschmann, Gwendolin (GIZ, 2020)

SystemCraft - a primer: How to Tackle our Toughest Problems - Simpson, Kate; Randall, Ian (Wasafiri, 2020)
Systemcraft is our applied framework to help leaders and organisations get started and keep going when faced with complex problems. It is built on our practical experience. It draws on a broad body of research, action and theory from the worlds of complexity thinking, systems theory, adaptive management, leadership development, social movements, development theory and beyond. Systemcraft has been designed to make systems thinking something any leader can apply when they find themselves faced with a complex problem and asking, ‘So what do I do next?’

A Pragmatic Approach to Assessing System Change - Posthumus, Hans; Shah, Rachel; Miehlbradt, Alexandra; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

A Pragmatic Approach to Assessing System Change: How to put it into practice - Miehlbradt, Alexandra; Shah, Rachel; Posthumus, Hans; Kessler, Adam (DCED, 2020)
Planning for and assessing system change is a strategic management issue. It is critical for everything from developing a strategy and designing interventions, to adapting strategy, improving implementation and reporting impact. But many programmes get stuck when it comes to assessing system change. The private sector development field has struggled to agree on an approach that programmes can implement and stakeholders can understand. However some mature programmes are starting to assess system change more effectively. Building on these emerging practices, this paper outlines a process that programmes can use to assess system changes regularly and practically. Two complementary papers: Overview and How to put it into practice The Overview summarises the approach and How to put it into practice provides more detailed implementation guidance, worked examples, and useful tips. The Overview explores how to: develop a system change strategy and intervention plans that lay the groundwork for system change assessment, including how to set system boundaries and how to identify the system changes a programme aims to catalyse assess system changes using both: - an intervention lens focused on changes introduced by specific interventions - a helicopter lens that provides a whole system view By analysing findings from both lenses, programmes can improve their strategy and report on their contribution to system change. How to put it into practice uses two case examples for illustration throughout the paper - PRISMA’s work in the maize system in East Java and Indonesia and S4J’s work in the Vocational Education and Training (VET) system in Albania. It targets practitioners responsible for facilitating and/or assessing system change. The paper explains how to: articulate the system changes that a programme aims to catalyse assess those changes use the results to inform decision making and reporting The approach described in the paper builds on the practices outlined in the DCED Results Measurement Standard. The guidance provided has been designed to be useful to programmes that aim to catalyse system changes whether or not they apply the DCED Standard.

System Innovation Network - Si Network (Si Network, 2020)
The Si Network is an online platform for building the developing of systems innovation - connecting people around the world to learn and apply the ideas and methods of systems innovation towards addressing complex challenges and building better systems that work for all. Not sure what systems innovation is? Systems innovation is a new approach to innovation that tries to tackle complex social and environmental challenges through the use of more holistic & innovation driven approaches. It is a kind of innovation that aims to change the underlying structure of a system, thus potentially enabling a more transformational kind of change - systems change - rather than incremental "innovation as usual". What Do You Do? We are building an ecosystem of individuals and organizations co-learning and co-creating systems innovation across geographies and sectors. This ecosystem is enabled by our online platform which provides educational content, toolkits, organizes events and projects as well as provides various support services for organizations. Purpose Statement Our purpose is to build the world’s capacity for systems innovation - so as to better understand and address complex challenges and co-create a world where systems work for all. We envision a world where everyone thinks in systems and has an understanding of complex systems. From this understanding, we are able to design and develop regenerative systems that work for everyone. Our mission is to grow the field of systems innovation as a pathway to co-learn the ideas of systems thinking and apply them to co-creating new systems Who's Involved? We are a networked organization of some 17K+ members forming part of 20+ hubs in major cities around the world. Our community is broad and diverse in areas of work and interest from designers, innovators, and entrepreneurs, to researchers and management but they all share a common interest in learning and applying systems thinking ideas. The Si platform is developed and managed by a small core team based in London UK. We are registered as a business but operate as a social enterprise focused on our purpose of advancing the area of systems innovation in theory and practice. Core Value Creativity - We put creativity at the centre of what we do. Holding a space for curiosity, diversity of views, exploration and critical thinking as a pathway to transformative innovation. Openness - We strongly believe in openness in our ways of being, thinking and organizing as a sustainable pathway to creating an adaptive, scalable and dynamic community. Growth Mindset - We embrace challenges as opportunities for continuous personal and collective learning and development, with a never-ending potential to grow and start with a new beginning. Perseverance - When facing uncertainty and failure, perseverance is what is needed to maintain commitment and a resilient pathway aligned with our purpose. Care - Care is one of our core principles. We foster relationships based on honesty and empathy, striving to be present and conscious in what we do and taking responsibility for the effects of our actions.